Australians in Aspic: Picturing Charmian Clift's and George Johnston's Expatriation - Dalziell, T.; Genoni, Paul (Journal of the Association for the Study of Australian Literature, 2015)
This paper considers how the expatriation of Australian authors Charmian Clift and George Johnston on the Greek island of Hydra has been represented photographically in a recently uncovered archive of over 1500 images. The photographs were taken by Life Magazine staff photographer James Burke in the summer of 1960. The analysis of the photographs is juxtaposed at key points with text from Clift's memoir Peel Me a Lotus, and the discussion focuses on the way the interplay between image and text produces supportive and/or contested representations of this particular experience of Australian literary expatriation.